Tabu dalam Bahasa Madura pada Masyarakat Montorna Kabupaten Sumenep - Nur Diana; Mawaddatul Jannah (Program Magister Linguistik Universitas Udayana, 2023)
Research on taboos in the Madurese language in the Montorna community, Sumenep district, is interesting to study, because taboo language in the Madurese language in the Montorna community, Sumenep district occurs frequently, even found almost every day. Both language taboos are related to spirits, and animal names, or because of the level of language used, and also because the understanding of words is determined by speech intonation and facial expressions. The purpose of this paper is to analyze taboo language in Madurese in the Montorna community, Sumenep district. This type of research is qualitative research that uses case studies. Data collection techniques used are observation, interviews, and field notes. Qualitative data were analyzed using descriptive methods. The results of this study are Knowing: 1). many kinds of Rude / Taboo Language in Maduranese, such as Animal Names spoken to other people, bad prayers, and so on 2). level of language in Maduranese and its use, such as yes'-enje', enggi-enten, or engghi-punten 3). understanding of words determined by speech intonation and facial expressions in the Montorna community, Sumenep district. The recommendation for further research is to provide solutions or ways of forming taboo language, in order to avoid it.